Startup performance from an economic development perspective: impact evaluation after funding stage - Partal, Mehmet Onur; Gonel, Feride (INDERSCIENCE ENTERPRISES LTD, 2025)
Startups, which are by nature different to traditional enterprises due to their innovative and technological features, are often defined as SMEs with the potential to grow rapidly. This study intends to explore the performance of startups from an economic development perspective. In this paper, a counterfactual impact evaluation will be implemented for a treatment group, which is funded by investors in Istanbul, Turkey. The results are compared to those of a control group. Employing difference in differences estimation, the comparison is based on a variety of indicators including employment, revenue, and profit generation in the ICT sector. Our results show us that the performance of funded startups positively diverges from the unfunded startups after the intervention period. At the end of this study, it is suggested that governments should motivate startups by acting as investors rather than grant allocators in the entrepreneurship ecosystem.
Keywords: government grants; subsidy; entrepreneurship; regional development; impact evaluation; financial support; firm performance; SMEs; startup; funds; Business & Economics